2021
DOI: 10.1021/acs.jmedchem.1c01336
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Discovery of Small Molecules Bound to T-Cell Immunoglobulin and Mucin Domain-Containing Molecule 3 (TIM-3)

Abstract: T-cell immunoglobulin and mucin domain-containing molecule 3 (TIM-3; HAVCR2) has emerged as an attractive immune checkpoint target for cancer immunotherapy. TIM-3 is a negative regulator of the systemic immune response to cancer and is expressed on several dysfunctional, or exhausted, immune cell subsets. Upregulation of TIM-3 is associated with tumor progression, poor survival rates, and acquired resistance to antibody-based immunotherapies in the clinic. Despite the potential advantages of small-molecule inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
0
24
1
Order By: Relevance
“…However, there are no table entries for papers targeting proteases, the first time this target class has not been represented. In contrast, there are more examples of GPCR case studies in Table than in previous years (entries 26, 27, and 28), including the description of the discovery of the M1 agonist clinical compound HTL9936 (entry 28). …”
Section: Resultsmentioning
confidence: 99%
“…However, there are no table entries for papers targeting proteases, the first time this target class has not been represented. In contrast, there are more examples of GPCR case studies in Table than in previous years (entries 26, 27, and 28), including the description of the discovery of the M1 agonist clinical compound HTL9936 (entry 28). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, the lock has been released. Rietz and coworkers have demonstrated that it is possible to directly target TIM-3 with specifically designed small heterocyclic molecules presenting nanomolar affinities of the receptor [ 95 ]. Alternatively, the TIM-3 checkpoint can be regulated with molecules that binds to the Gal-9 ligand, such as the disaccharide lactose.…”
Section: Discussionmentioning
confidence: 99%
“…Third and more interestingly, small molecule fragments capable of interacting with TIM-3 have been recently identified through an NMR-based fragment screen and optimized. Starting from low-affinity fragments such as the tricyclic triazoloquinazolinone unit (K D = 810 µM), the authors designed and synthesized high-affinity TIM-3 small-molecule ligands, such as compound the sulfonamide derivative 35 ( Figure 4 ) with a strongly reinforced affinity for TIM-3 (K i = 156 nM) [ 95 ]. This is a clever and promising approach toward the discovery of TIM-3-targeted therapeutics, even if at present the anticancer potential of these molecules has not been reported.…”
Section: Small Molecules Targeting Tim-3/gal-9 Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectroscopy is widely used in studies of structure–activity relationships (SAR) of potential lead compounds and in fragment-based drug discovery (FBDD). 19 F-probes are attractive because of the wide chemical shift range of 19 F-NMR, the high sensitivity of 19 F for NMR detection, and the absence of background 19 F-NMR signals in natural biological samples. In the limiting situation where exchange between bound and free ligand is slow on the chemical shift time scale, displacement of the probe molecule from its binding site can be measured by the decrease of the NMR signal intensity for the bound state (Figure S1).…”
mentioning
confidence: 99%